"y''-16y'+64y=-2x^2-5e^{5x}"
Let us solve a characteristic equation:
"k^2-16k+64=0"
"(k-8)^2=0"
"k_1= k_2=8"
The general solution is of the following form:
"y(x)=e^{8x}(C_1+C_2 x)+y_p(x)," where "y_p(x)" is a particular solution, "C_1, C_2" are arbitrary constants.
The particular solution has the following form:
"y_p(x)=ax^2+bx+c+de^{5x}", where "a,b,c" and "d" are constants.
"y_p'=2ax+b+5de^{5x}"
"y_p''=2a+25de^{5x}"
Put founded derivatives in the differential equation:
"2a+25de^{5x}-16(2ax+b+5de^{5x})+64(ax^2+bx+c+de^{5x})=-2x^2-5e^{5x}"
"2a+25de^{5x}-32ax-16b-80de^{5x}+64ax^2+64bx+64c+64de^{5x}=-2x^2-5e^{5x}"
"64ax^2+(-32a+64b)x+(2a-16b+64c)+9de^{5x}=-2x^2-5e^{5x}"
Equating the corresponding coefficients, we obtain a system of equations:
"\\begin{cases} 64a=-2\\\\ -32a+64b=0\\\\2a-16b+64c=0\\\\9d=-5 \\end{cases}"
"\\begin{cases} a=-\\frac{1}{32}\\\\ a=2b\\\\64c=-2a+16b\\\\9d=-5 \\end{cases}"
"\\begin{cases} a=-\\frac{1}{32}\\\\ b=-\\frac{1}{64}\\\\64c=\\frac{1}{16}-\\frac{1}{4}\\\\d=-\\frac{5}{9} \\end{cases}"
"\\begin{cases} a=-\\frac{1}{32}\\\\ b=-\\frac{1}{64}\\\\c=-\\frac{3}{1024}\\\\d=-\\frac{5}{9} \\end{cases}"
Finally, the solution of the differential equation is the following:
"y(x)=e^{8x}(C_1+C_2 x)-\\frac{1}{32}x^2-\\frac{1}{64}x-\\frac{3}{1024}-\\frac{5}{9}e^{5x}"
Comments
Leave a comment